Compulsive treatment of alcohol addicts: the perspective of legal and ethical dilemmas - Kmieciak, Błażej (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
In Poland, the provisions of the Act on Counteracting Alcoholism and Upbringing in Sobriety have been in force for more than three decades. It is hard to overstate the social impact this document has had since its emergence. In the 1970’s and 1980’s one could notice a clear correlation between the increase in the level of alcohol consumption and the emergence of increasingly serious crises within families. The anti-alcohol law was to introduce significant standards for the sale of alcohol products. At the same time it set up the principles of directing addicts to compulsory therapy, which have been in effect ever since. The topic of compulsory treatment of people addicted to alcohol is still widely discussed in both legal, medical and psycho-pedagogical literature. Some claim that only voluntary participation in therapy allows one to begin an effective recovery process. On the other hand, we are also reminded that in the case of alcohol addiction it is often not possible to obtain the patient’s consent for treatment. It is noted that continuing addiction inevitably leads to the suffering of the family of the addict. Moreover, a person in a such a condition is said to be “enslaved” by alcohol. This prevents him from making rational decisions, crucial for him and his relatives. In Poland, compulsory hospital treatment for addicts (with exceptions) can only be applied to persons who have been diagnosed with alcohol dependency syndrome. Are such activities still justified? Is this action intended solely to protect the health of the addict? Perhaps the position of the addicted person’s family is of key importance is in this regard? The aim of the article is to present deliberations on these questions.